Surface Protection Systems for Reinforced Concrete in Marine Environments: A 2019–2025 Scoping Review on Chloride Ingress Mitigation and Corrosion Resistance - Roesdiana, Tira (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2026)
Chloride-induced reinforcement corrosion is a dominant degradation mechanism in reinforced concrete structures located in coastal and marine regions, leading to cracking, spalling, performance deterioration, and reduced service life. Various surface protection systems including coatings, surface modification, and material-based approaches to enhance ion-transport resistance have been developed as barriers to reduce chloride ingress and delay corrosion initiation. This study presents a scoping review of the 2019–2025 literature to map research directions, commonly used evaluation indicators, and evidence gaps in assessing the performance of surface protection for reinforced concrete in marine environments. The synthesis is organized thematically according to: (i) types of protection systems (alternative-binder-based coatings, hybrid coatings, and supporting durability approaches), (ii) evaluation indicators (pull-off adhesion, water absorption/sorptivity, chloride migration/diffusion parameters, electrochemical corrosion indicators, and microstructural characterization), and (iii) exposure protocols (immersion, wet–dry cycles, NaCl/seawater, and other aggressive environments). The literature indicates growing attention to more sustainable surface protection strategies, particularly those based on alternative binders and surface modification to improve stability and mitigate phenomena such as efflorescence. However, inconsistent testing protocols, limited long-term/field validation, and the still-weak linkage between microstructural evidence and chloride transport parameters as well as electrochemical corrosion responses remain major challenges. The proposed research agenda includes standardizing a “minimum evidence set,” strengthening interface and microcrack evaluation, and integrating microstructure transport corrosion indicators to support more reliable recommendations for coastal infrastructure.